2001
DOI: 10.1001/archpsyc.58.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Paternal Age and the Risk of Schizophrenia

Abstract: These findings support the hypothesis that schizophrenia may be associated, in part, with de novo mutations arising in paternal germ cells. If confirmed, they would entail a need for novel approaches to the identification of genes involved in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
383
8
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(430 citation statements)
references
References 36 publications
(24 reference statements)
28
383
8
6
Order By: Relevance
“…Therefore, there must be a genetic mechanism to supply causal factors to balance the negative selection. DNMs, defi ned as mutations arising sporadically either in the germ-line of the parents or at an early stage of embryonic development so that the mutations are only detected in affected individual but not in the parents, was proposed many years ago as a mechanism to offset the negative selection [68] . This proposition was based on the epidemiological observation that paternal age is associated with an increased risk of SCZ [69][70][71] .…”
Section: De Novo Mutations In Sczmentioning
confidence: 99%
“…Therefore, there must be a genetic mechanism to supply causal factors to balance the negative selection. DNMs, defi ned as mutations arising sporadically either in the germ-line of the parents or at an early stage of embryonic development so that the mutations are only detected in affected individual but not in the parents, was proposed many years ago as a mechanism to offset the negative selection [68] . This proposition was based on the epidemiological observation that paternal age is associated with an increased risk of SCZ [69][70][71] .…”
Section: De Novo Mutations In Sczmentioning
confidence: 99%
“…We relied on an ongoing, population-based cohort study of individuals born in 1964-76 (Harlap et al 2006;Malaspina et al 2001). The Jerusalem Perinatal Study included all births to mothers in a defined geographic area, recording demographic data on the parents, including their occupations from the birth certificate.…”
Section: Subjectsmentioning
confidence: 99%
“…To study schizophrenia, the cohort was linked to Israel's national Psychiatric Registry. This registry, established in 1950, receives psychiatric diagnoses from multiple sources, including inpatient wards in psychiatric and general hospitals, and psychiatric day-care facilites (Malaspina et al 2001). Diagnoses for individuals with psychosis have been validated (Weiser et al 2005).…”
Section: Subjectsmentioning
confidence: 99%
“…Growing evidence suggests that, independent of maternal age, the offspring of older fathers are more susceptible to a wide range of conditions (Goriely et al, 2012). Studies have shown consistent associations of advanced paternal age (APA) with an increased risk of schizophrenia in offspring (Malaspina et al, 2001) as well as a range of other psychiatric morbidities, such as autism spectrum disorders (Grether et al, 2009;Hultman et al, 2011), bipolar disorder (Frans et al, 2008), epilepsy (Vestergraad et al, 2005), obsessivecompulsive disorder (Wu et al, 2012) and reduced cognitive abilities in infancy and childhood (Saha et al, 2009). There appears to remain a notable lack of consensus on how to define what constitutes advanced paternal age itself.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated mutations and chromosomal anomalies in reproductive germ cells might account for the largest part of the risk of mental disorders associated with advanced paternal age (Goriely et al, 2013). New mutations may explain why schizophrenia is maintained in the population, despite the significant reproductive disadvantages of affected individuals (Malaspina et al, 2001). …”
Section: Introductionmentioning
confidence: 99%